Evaluating the Efficacy of Some Disinfectants, Sterilizers and Detergents Against Streptococcus Pyogenes Isolates from Tonsillitis Patient in Kirkuk City - Aylan Arslan Ali1 , Shymaa Hassan Ali2 (Institute of Medico-legal Publications Pvt Ltd, 2021)
The aim of the study was to evaluate the inhibitory effectiveness of some disinfectants, sterilizers anddetergents commonly used, including: Dettol (Sabtol( ,Bleach, ethanol alcohol, liquid soap, dishwashingliquid, ActiveX and Sterile Gel 85 on bacterial growth Streptococcus pyogenes, The study includedcollecting (150) swabs from Patients referred to the hospital and from private medical laboratories (agegroups were16-40 years) ,the swabs were taken by (Transport media) containing the prepared agriculturalmedium and transported to the laboratory for the purpose of isolation and diagnosis.The results of the bacterial sensitivity test under study for these disinfectants, sterilizers and detergentsaccording to the type and concentrations of the preparation (50,25,12.5)%, and that alcohol ethanol,hypochlorite sodium and sterile gel(Gel 85)have a high effect on the growth of bacteria Streptococcuspyogenes and with all the concentrations prepared, and while detergents Liquid and liquid soap, dishwashing,had less effect on the bacteria under study, according to the prepared concentrations.